2011
DOI: 10.1111/j.1447-0756.2011.01572.x
|View full text |Cite
|
Sign up to set email alerts
|

Rate of negative appendectomy in pregnant women in Benin City, Nigeria

Abstract: While a higher index of suspicion among clinicians will ensure earlier diagnosis and improve the associated maternal and fetal prognosis, the need to reduce the negative laparotomy rate is highlighted by the high rate of adverse obstetric outcomes amongst the negative appendectomy group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Most previous cross-sectional studies have attempted to identify clinical features and postoperative maternal and fetal outcomes and/or described the best diagnostic tools and surgical treatments for acute appendicitis, using data collected on few patients from single centers, [8][9][10][11][12][13][14][15]19,20 with only 3 previous studies using national registers. [16][17][18] The rate of acute appendicitis reported during the antepartum period in our study (6.3 per 10,000 person-years) was between that reported in 2 prior population-based studies (2.4 and 9.25 per 10,000 person-years).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous cross-sectional studies have attempted to identify clinical features and postoperative maternal and fetal outcomes and/or described the best diagnostic tools and surgical treatments for acute appendicitis, using data collected on few patients from single centers, [8][9][10][11][12][13][14][15]19,20 with only 3 previous studies using national registers. [16][17][18] The rate of acute appendicitis reported during the antepartum period in our study (6.3 per 10,000 person-years) was between that reported in 2 prior population-based studies (2.4 and 9.25 per 10,000 person-years).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…7 Current estimates of the incidence of acute appendicitis in pregnancy are inconsistent and vary widely ranging from 1.8 to 41 per 10,000 pregnancies. [8][9][10][11][12][13][14][15][16][17][18] In particular, the trimester of pregnancy during which a woman is at highest risk of acute appendicitis and the extent to which age affects these risks are poorly understood. [8][9][10][11][12][13][14][15][16][17][18] In addition, there is no population-based study to date reporting the incidence rates of acute appendicitis during the postpartum period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that this approach could result in a negative appendectomy in 11% to 50% of cases. While negative appendectomy is acceptable to a certain extent, it is also unclear whether negative appendectomy or complicated appendicitis may be associated with unfavorable fetal and pregnancy outcomes (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…5 However, a recent study reported that higher rates of adverse obstetric outcomes were observed amongst pregnant women with negative appendectomy. 6 Ultrasonography (USG) is a non-invasive and inexpensive test, which does not expose the patient to radiation, and is reported to have sensitivity and specificity of 86 and 81% for the diagnosis of acute appendicitis, respectively. 7 The major disadvantage of USG is its operator dependent character.…”
Section: Introductionmentioning
confidence: 99%